2021
DOI: 10.1093/ajcn/nqab062
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancing the cardiovascular protective effects of a healthy dietary pattern with wolfberry (Lycium barbarum): A randomized controlled trial

Abstract: Background The consumption of wolfberry (Lycium barbarum), a rich source of carotenoids and bioactive polysaccharides, may serve as a potential dietary strategy for cardiovascular disease (CVD) risk management although limited studies examined its effects as whole fruits. Objectives To investigate the impact of wolfberry consumption as part of a healthy dietary pattern on vascular health-related outcomes and classical CVD ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Due to limited evidence on the health effects of whole dried fruits, considering possible synergism among bioactive compounds, Toh et al (2021) investigated the effects of healthy dietary patterns, either with or without whole dried wolfberry (15 g/d), in middle-aged and older adults. They demonstrated that adherence to a healthy dietary pattern based on whole grains, fruits, non-starchy vegetables, and non-processed meats improves vascular tone, while incorporating goji berry into the diet further improves the blood lipid-lipoprotein profile, and may lower long-term cardiovascular risk [ 94 ]. In addition, they observed an inverse association between the changes in plasma zeaxanthin and plasma 8-iso-prostaglandin F2α.…”
Section: Health Benefits and Side Effects Of Goji Berry Consumptionmentioning
confidence: 99%
“…Due to limited evidence on the health effects of whole dried fruits, considering possible synergism among bioactive compounds, Toh et al (2021) investigated the effects of healthy dietary patterns, either with or without whole dried wolfberry (15 g/d), in middle-aged and older adults. They demonstrated that adherence to a healthy dietary pattern based on whole grains, fruits, non-starchy vegetables, and non-processed meats improves vascular tone, while incorporating goji berry into the diet further improves the blood lipid-lipoprotein profile, and may lower long-term cardiovascular risk [ 94 ]. In addition, they observed an inverse association between the changes in plasma zeaxanthin and plasma 8-iso-prostaglandin F2α.…”
Section: Health Benefits and Side Effects Of Goji Berry Consumptionmentioning
confidence: 99%
“…However, this beneficial effect was only observed with long-term tomato consumption (at least one week) but not with acute feeding. In addition, no favorable effect on FMD was found from consuming Goji berry, which is rich in zeaxanthin [ 85 ].…”
Section: Randomized Controlled Trials On Carotenoids and Cvdsmentioning
confidence: 99%
“…On the contrary, 12 months of astaxanthin supplementation failed to result in a significant improvement in IMT with healthy participants [ 91 ]. Moreover, Toh et al [ 85 ] reported no significant reduction in IMT after consuming Goji berry for 16 weeks in relatively healthy middle-aged and older adults. This was possibly because subjects who were diagnosed with subclinical atherosclerosis had an elevated IMT at baseline compared with healthy subjects.…”
Section: Randomized Controlled Trials On Carotenoids and Cvdsmentioning
confidence: 99%
“…The length of a fresh wolfberry is 1–2 cm and the annual production can reach 0.26 million tons; most of them are consumed and applicated after being dried [ 2 , 3 ]. Pharmacological studies have shown that polysaccharides, total phenols, total flavonoids, and other functional compounds in drying-processed wolfberries are immune-supportive, anti-tumorigenic, and have anti-aging effects [ 4 , 5 ]. The moisture content of ripe, fresh wolfberry fruit can reach more than 80%, and the fruit has a high sugar content and is sensitive to microbial deterioration, causing it to rot easily during harvest and storage [ 6 ].…”
Section: Introductionmentioning
confidence: 99%